Opening Wedge Osteotomy for Distal Radius Malunion: Dorsal or Palmar Approach? - Rothenfluh, Esin; Schweizer, Andreas; Nagy, Ladislav (Journal of Wrist Surgery, 2013)
Background There are various technical variations to consider when performing a corrective osteotomy of a distal radius malunion. We chose two of the more commonly reported techniques and compared the results of volar (palmar) osteotomy and fixation with dorsal osteotomy and fixation.Method Within a continuous cohort of patients who had undergone corrective osteotomy for a malunited Colles fracture, two groups could be identified retrospectively. In 8 patients a dorsal approach was used. A structural trapezoidal graft, subtending the amount of correction, was inserted into the osteotomy gap and stabilization was performed with a thin round-hole mini-fragment plate. In 14 patients a palmar approach and a palmar fixed-angle plate was used for correction of the malunion and for angular stable rigid fixation of the two fragments. The osteotomy gap was loosely filled with nonstructural cancellous bone chips.A retrospective comparison of the two groups was performed to see whether the outcome was affected by the use of either operative technique.The demographics, the preoperative amount of deformity, range of motion, pain, and force were comparable for both groups. All osteotomies healed without loss of correction.After a minimal follow-up of one year, radiographic appearance, objective functional parameters were assessed and subjective data (Disabilities of the Arm, Shoulder, and Hand [DASH] score and special pain and function questionnaire) obtained.Results These data did not show statistical difference for the two groups except for the amount of final wrist flexion. This parameter was significantly better in patients who had palmar approaches and fixed-angle plates.Conclusion Corrective osteotomies of distal radius malunions can be done in either way. It might result in some better flexion, if performed volarly.
Keywords: distal radius; malunion; corrective osteotomy; palmar approach; dorsal approach